Rhodium-catalyzed intramolecular reductive aldol-type cyclization: Application for the synthesis of a chiral necic acid lactone - Isoda, Motoyuki; Sato, Kazuyuki; Kameda, Kenta; Wakabayashi, Kana; Sato, Ryota; Minami, Hideki; Karuo, Yukiko; Tarui, Atsushi; Kawai, Kentaro; Omote, Masaaki (Beilstein Journal of Organic Chemistry, 2022)
A rhodium-catalyzed intramolecular reductive aldol-type cyclization is described to give β-hydroxylactones with high diastereoselectivities. The stereoselectivity of this cyclization is highly solvent dependent and can give syn- or anti-β-hydroxylactones with high diastereoselectivity. This methodology was also applied to the synthesis of a chiral necic acid lactone which is a structural component of the pyrrolizidine alkaloid monocrotaline.
Keywords: β-hydroxylactone; intramolecular reductive aldol cyclization; necic acid lactone; rhodium catalyst

(untitled) - Volla, C. M. R.; Atodiresei, I.; Rueping, M. (Chem. Rev., 2014)

(untitled) - Roscales, S.; Csákÿ, A. G. (Chem. Soc. Rev., 2014)

(untitled) - Thankachan, A. P.; Asha, S.; Sindhu, K. S.; Anilkumar, G. (RSC Adv., 2015)

(untitled) - Brahmachari, G. (RSC Adv., 2016)

(untitled) - Becker, M. R.; Watson, R. B.; Schindler, C. S. (Chem. Soc. Rev., 2018)

(untitled) - Kwiatkowski, M. R.; Alexanian, E. J. (Acc. Chem. Res., 2019)

(untitled) - Ye, S.; Xiang, T.; Li, X.; Wu, J. (Org. Chem. Front., 2019)

(untitled) - Rej, S.; Ano, Y.; Chatani, N. (Chem. Rev., 2020)

(untitled) - Ochi, Y.; Yokoshima, S.; Fukuyama, F. (Synthesis, 2017)

(untitled) - Xiao, Z.; Li, Y.; Gao, S. (Org. Lett., 2017)

(untitled) - Yuan, P.; Liu, X.; Yang, X.; Zhang, Y.; Chen, X. (J. Org. Chem., 2017)

(untitled) - Wolleb, H.; Carreira, E. M. (Angew. Chem., Int. Ed., 2017)

(untitled) - Zhang, Q.; Zhang, Z.; Huang, Z.; Zhang, C.; Xi, S.; Zhang, M. (Angew. Chem., Int. Ed., 2018)

(untitled) - Abe, H.; Fujimaki, M.; Nakagawa, E.; Kobayashi, T.; Ito, H. (Chem. Commun., 2018)

(untitled) - Kalmode, H. P.; Handore, K. L.; Rajput, R.; Shaikh, S. R.; Gonnade, R. G.; Kulkarni, K. A.; Reddy, D. S. (Org. Lett., 2018)

(untitled) - Kawamoto, Y.; Ozone, D.; Kobayashi, T.; Ito, H. (Org. Biomol. Chem., 2018)

(untitled) - Tsukamoto, H.; Hanada, S.; Nomura, Y.; Doi, T. (J. Org. Chem., 2018)

(untitled) - Kalmode, H. P.; Patil, S. S.; Handore, K. L.; Athawale, P. R.; Dandela, R.; Verma, A. K.; Basu, A.; Reddy, D. S. (Eur. J. Org. Chem., 2019)

(untitled) - Isayama, S.; Mukaiyama, T. (Chem. Lett., 1989)

(untitled) - Lam, H. W.; Joensuu, P. M.; Murray, G. J.; Fordyce, E. A. F.; Prieto, O.; Luebbers, T. (Org. Lett., 2006)

(untitled) - Lumby, R. J. R.; Joensuu, P. M.; Lam, H. W. (Org. Lett., 2007)

(untitled) - Chiu, P.; Chen, B.; Cheng, K. F. (Tetrahedron Lett., 1998)

(untitled) - Ooi, T.; Doda, K.; Sakai, D.; Maruoka, K. (Tetrahedron Lett., 1999)

(untitled) - Deschamp, J.; Chuzel, O.; Hannedouche, J.; Riant, O. (Angew. Chem., Int. Ed., 2006)

(untitled) - Kato, M.; Oki, H.; Ogata, K.; Fukuzawa, S. (Synlett, 2009)

(untitled) - Chrovian, C. C.; Montgomery, J. (Org. Lett., 2007)

(untitled) - Kiyooka, S.-i.; Shimizu, A.; Torii, S. (Tetrahedron Lett., 1998)

(untitled) - Zhao, C.-X.; Duffey, M. O.; Taylor, S. J.; Morken, J. P. (Org. Lett., 2001)

(untitled) - Shibahara, F.; Krische, M. J. (Chem. Lett., 2008)

(untitled) - Kawakami, T.; Miyatake, M.; Shibata, I.; Baba, A. (J. Org. Chem., 1996)

(untitled) - Węglarz, I.; Szewczyk, M.; Mlynarski, J. (Adv. Synth. Catal., 2020)

(untitled) - Meyer, C. C.; Ortiz, E.; Krische, M. J. (Chem. Rev., 2020)

(untitled) - Revis, A.; Hilty, T. K. (Tetrahedron Lett., 1987)

(untitled) - Taylor, S. J.; Morken, J. P. (J. Am. Chem. Soc., 1999)

(untitled) - Emiabata-Smith, D.; McKillop, A.; Mills, C.; Motherwell, W. B.; Whitehead, A. J. (Synlett, 2001)

(untitled) - Jang, H.-Y.; Huddleston, R. R.; Krische, M. J. (J. Am. Chem. Soc., 2002)

(untitled) - Nishiyama, H.; Shiomi, T.; Tsuchiya, Y.; Matsuda, I. (J. Am. Chem. Soc., 2005)

(untitled) - Shiomi, T.; Nishiyama, H. (Org. Lett., 2007)

(untitled) - Bee, C.; Han, S. B.; Hassan, A.; Iida, H.; Krische, M. J. (J. Am. Chem. Soc., 2008)

(untitled) - Shiomi, T.; Adachi, T.; Ito, J.-i.; Nishiyama, H. (Org. Lett., 2009)

(untitled) - Sato, K.; Yamazoe, S.; Yamamoto, R.; Ohata, S.; Tarui, A.; Omote, M.; Kumadaki, I.; Ando, A. (Org. Lett., 2008)

(untitled) - Sato, K.; Isoda, M.; Ohata, S.; Morita, S.; Tarui, A.; Omote, M.; Kumadaki, I.; Ando, A. (Adv. Synth. Catal., 2012)

(untitled) - Sato, K.; Isoda, M.; Tokura, Y.; Omura, K.; Tarui, A.; Omote, M.; Kumadaki, I.; Ando, A. (Tetrahedron Lett., 2013)

(untitled) - Isoda, M.; Sato, K.; Tokura, Y.; Tarui, A.; Omote, M.; Ando, A. (Chem. Pharm. Bull., 2014)

(untitled) - Isoda, M.; Sato, K.; Funakoshi, M.; Omura, K.; Tarui, A.; Omote, M.; Ando, A. (J. Org. Chem., 2015)

(untitled) - Isoda, M.; Sato, K.; Kunugi, Y.; Tokonishi, S.; Tarui, A.; Omote, M.; Minami, H.; Ando, A. (Beilstein J. Org. Chem., 2016)

(untitled) - Sato, K.; Isoda, M.; Tarui, A.; Omote, M. (Eur. J. Org. Chem., 2020)

(untitled) - Kawashima, S.; Aikawa, K.; Mikami, K. (Eur. J. Org. Chem., 2016)

(untitled) - Pavlovic, L.; Vaitla, J.; Bayer, A.; Hopmann, K. H. (Organometallics, 2018)

(untitled) - Lu, S.; Sun, P.; Li, T.; Kurtán, T.; Mándi, A.; Antus, S.; Krohn, K.; Draeger, S.; Schulz, B.; Yi, Y.; Li, L.; Zhang, W. (J. Org. Chem., 2011)

(untitled) - Tang, Y.-Q.; Sattler, I.; Thiericke, R.; Grabley, S. (J. Antibiot., 2000)

(untitled) - Verdan, M. H.; Barison, A.; Lemos de Sá, E.; Salvador, M. J.; Poliquesi, C. B.; Eberlin, M. N.; Stefanello, M. É. A. (J. Nat. Prod., 2010)

(untitled) - Neal, W. M.; Rusoff, L. L.; Ahmann, C. F. (J. Am. Chem. Soc., 1935)

(untitled) - Vedejs, E.; Ahmad, S.; Larsen, S. D.; Westwood, S. (J. Org. Chem., 1987)

(untitled) - Niwa, H.; Okamoto, O.; Yamada, K. (Tetrahedron Lett., 1988)

(untitled) - Niwa, H.; Ogawa, T.; Okamoto, O.; Yamada, K. (Tetrahedron, 1992)

(untitled) - Honda, T.; Tomitsuka, K.; Tsubuki, M. (J. Org. Chem., 1993)

(untitled) - Shao, H.; Rueter, J. K.; Goodman, M. (J. Org. Chem., 1998)

(untitled) - Weber, F.; Brückner, R. (Org. Lett., 2014)